Tipologi strategi hibrida dalam membentuk karakter sahabat Al-Qur'an di Madrasah Aliyah - Wicaksono, Aulia Tegar; Abdullah, Mulyana; Subakti, Ganjar Eka (Idarah Tarbawiyah: Journal of Management in Islamic Education, 2026)
The disparity between functional literacy skills and the internalization of Quranic values among Generation Z students presents a critical challenge for Islamic education in the digital era. This study aims to identify and map the comprehensive strategies implemented by Islamic Senior High Schools (Madrasah Aliyah) in transforming students with low baseline proficiency into individuals embodying the character of Sahabat Al-Qur'an (Companions of the Quran). Utilizing a qualitative multi-site case study design, data were collected through in-depth interviews and documentation across ten different schools. The analysis reveals that these schools do not rely on monolithic approaches but rather apply a Hybrid Strategy Typology comprising three dimensions: (1) Structural-Disciplinary Strategy, which utilizes strict regulations and parental involvement to enforce initial habituation; (2) Humanist-Exemplary Strategy, which fosters intrinsic motivation through teacher role-modeling and emotional bonding; and (3) Cultural-Environmental Strategy, which engineers physical and digital ecosystems. Significant findings indicate a strategic polarization regarding technology, where some schools adopt a Digital Detox while others pursue Digital Utilization through reflective media analysis. The study concludes that effective character formation requires the simultaneous orchestration of external discipline, psychological support, and adaptive environmental engineering, signaling the need for a shift from teacher-centered instruction toward activity centered student engagement. Abstrak Kesenjangan antara kemampuan literasi fungsional dan internalisasi nilai-nilai Al-Qur'an di kalangan siswa Generasi Z menghadirkan tantangan kritis bagi pendidikan Islam di era digital. Penelitian ini bertujuan untuk mengidentifikasi dan memetakan strategi komprehensif yang diterapkan oleh Madrasah Aliyah dalam mentransformasi siswa dengan kemampuan dasar rendah menjadi individu yang berkarakter Sahabat Al-Qur'an. Menggunakan desain studi kasus multi-situs kualitatif, data dikumpulkan melalui wawancara mendalam dan dokumentasi di sepuluh Madrasah Aliyah yang berbeda. Analisis data mengungkapkan bahwa sekolah tidak bergantung pada pendekatan monolitik, melainkan menerapkan Tipologi Strategi Hibrida yang terdiri dari tiga dimensi: (1) Structural-Disciplinary Strategy, yang menggunakan regulasi ketat dan pelibatan orang tua untuk memaksakan pembiasaan awal; (2) Humanist-Exemplary Strategy, yang menumbuhkan motivasi intrinsik melalui keteladanan guru dan ikatan emosional; dan (3) Cultural-Environmental Strategy, yang merekayasa ekosistem fisik dan digital. Temuan signifikan menunjukkan adanya polarisasi strategis terkait teknologi, di mana sebagian sekolah mengadopsi Digital Detox sementara yang lain mengejar Digital Utilization melalui analisis media reflektif. Studi ini menyimpulkan bahwa pembentukan karakter yang efektif memerlukan orkestrasi simultan antara disiplin eksternal, dukungan psikologis, dan rekayasa lingkungan adaptif, yang menandakan perlunya pergeseran dari instruksi berpusat pada guru menuju keterlibatan siswa yang berpusat pada aktivitas.